2014
DOI: 10.1002/dac.2823
|View full text |Cite
|
Sign up to set email alerts
|

Blind carrier frequency offset mitigation in space–time block‐coded multicarrier code division multiple access uplink transmission

Abstract: In this paper, a novel blind carrier frequency offset (CFO) estimation is proposed on the basis of the linearly constrained optimization for the uplink transmission of space-time block-coded multicarrier code division multiple access systems. First, the full-dimensional spatial-and-temporal data are formed to avoid violation of the second-order statistics in the conventional receiver design. A set of weight vectors is then provided for acquiring each multipath signal from the desired user while the others get … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It can be found that the quadratic cost function with respect to in (7) reaches a minimum value while the condition of = 0 is satisfied [26]. In this way, the CFO estimate can be implemented by searching the minimum of the cost function.…”
Section: Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that the quadratic cost function with respect to in (7) reaches a minimum value while the condition of = 0 is satisfied [26]. In this way, the CFO estimate can be implemented by searching the minimum of the cost function.…”
Section: Estimationmentioning
confidence: 99%
“…SubstitutingL in (26) andˆ 0 in (29) into (23), we have the trimming estimate of the channel response.…”
Section: Proposed Joint Cfo and Channel Estimationmentioning
confidence: 99%